Quantitative assessment of oligomeric amyloid β peptide binding to α7 nicotinic receptor. (20th May 2019) - Cecon, Erika; Dam, Julie; Luka, Marine; Gautier, Clément; Chollet, Anne‐Marie; Delagrange, Philippe; Danober, Laurence; Jockers, Ralf
Abstract : Background and Purpose: Progressive dysfunction of cholinergic transmission is a well‐known characteristic of Alzheimer's disease (AD). Amyloid β (Aβ) peptide oligomers are known to play a central role in AD and are suggested to impair the function of the cholinergic nicotinic ACh receptor α7 (α7nAChR). However, the mechanism underlying the effect of Aβ on α7nAChR function is not fully understood, limiting the therapeutic exploration of this observation in AD. Here, we aimed to detect and characterize Aβ binding to α7nAChR, including the possibility of interfering with this interaction for therapeutic purposes. Experimental Approach: We developed a specific and quantitative time‐resolved FRET (TR‐FRET)‐based binding assay for Aβ to α7nAChR and pharmacologically characterized this interaction. Key Results: We demonstrated specific and high‐affinity (low nanomolar) binding of Aβ to the orthosteric binding site of α7nAChR. Aβ binding was prevented and reversed by the well‐characterized orthosteric ligands of α7nAChR (epibatidine, α‐bungarotoxin, methylylcaconitine, PNU‐282987, S24795, and EVP6124) and by the type II positive allosteric modulator (PAM) PNU‐120596 but not by the type I PAM NS1738. Conclusions and Implications: Our TR‐FRET Aβ binding assay demonstrates for the first time the specific binding of Aβ to α7nAChR, which will be a crucial tool for the development, testing, and selection of a novel generation of AD drug candidates targeting Aβ/α7nAChR complexes with high specificity and fewer side effects compared to currently approved α7nAChR drugs. Linked Articles: This article is part of a themed section on Therapeutics for Dementia and Alzheimer's Disease: New Directions for Precision Medicine. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.18/issuetoc